Median arcuate ligament syndrome: a cost analysis to determine the economic burden of a rarely diagnosed disease - Skelly, Christopher L.; Stiles-Shields, Colleen; Goldenthal, Hayley; Bohr, Nicole; Feldman, Estee; Mak, Grace Zee; Drossos, Tina (Frontiers in Psychology, 2024)
Background Chronic abdominal pain (CAP) is a medical condition resulting in enormous economic burden and healthcare utilization costs. One understudied source of CAP is the median arcuate ligament syndrome (MALS). MALS is often not diagnosed and treated for a variety of reasons, including the fact that MALS is highly comorbid with psychological symptoms and psychiatric disorders similar to CAP. To better inform future work on the study of MALS, we undertook a pilot study to estimate the economic impact and public health burden of this condition. We hypothesized that MALS imposes a significant public health burden. Methods Pediatric and adult patients enrolled in a prospective study undergoing multidisciplinary evaluation and treatment for MALS at a tertiary care facility were invited to participate in a brief self-report survey, the Direct and Indirect Medical Care Impact of MALS Form, to capture health care resources including procedures, surgeries, health care visits, and absenteeism (school and work). To estimate costs from the Direct and Indirect Medical Care Impact of MALS Form, the medical care usage data self-reported by patients were converted to dollar value utilizing FSC-93 billing data and corresponding current procedural terminology (CPT) codes for procedures and provider visits one year prior to surgery and then following surgery. Descriptive analyses were conducted to characterize the sample in terms of demographics and reported absences from school and work. Results One hundred and nineteen patients (mean age = 30.9 ± 13.0) completed the questionnaires, yielding a 57% response rate. 82.4% (n = 98) of the participants were female and 90.8% (n = 108) were non-Hispanic/Latine white. The mean and median surgical follow-up periods were 5.3 and 5.4 years, respectively. Overall, median cost of provider and ancillary healthcare provider visits for each patient was (US)$19,119 including the pre-operative and post-operative visits. The mean cost for providers alone was (US)$28,908. Wilcoxon signed-ranks tests indicated that the postoperative missed number of days of school were significantly lower than the pre-surgical number of missed school days (Z = −3.36, p = 0.001). Similarly, there were significantly less missed work-days following surgery than before for the entire sample (Z = −2.86, p = 0.004). Conclusion Median arcuate ligament syndrome imposes a large economic burden on patients and the healthcare system. The current findings, although reflective of a homogenous population, are adding to a growing body of literature suggesting that healthcare disparities play a role in the low rates of diagnosis and treatment of MALS.